Hesitancy to Seek Help Millennial Generation in Surabaya - Nadya Angelica; Dewi Astuti; Evelyn Evelyn (Accounting Study Program, Universitas Ciputra Surabaya, 2019)
This study aims to determine the effect of financial issue involvement, subjective financial knowledge, grit, financial health self efficacy, and financial stressed on hesitancy to help in the millennial generation in Surabaya. The method used in this research is quantitative research methods. The sample in this study were 100 respondents taken by purposive sampling method. Data analysis will be carried out using partial least square with the help of SmartPLS version 3. The results of the study show that financial issue involvement, subjective financial knowledge, and grit have a significant effect on financial health self efficacy, but financial health self efficacy has no significant effect on hesitancy to seek help. Financial stressed has a significant effect on hesitancy to seek help.